ANALISIS PENDAPATAN USAHA TANI STOBERI DI TEMPAT WISATA D’MOOAT DESA MOAT KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR - Shierly Angelina Stephanie Suprianto; Agnes Estephina Loho; Benny Adrian Berthy Sagay (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the income of strawberry farming in the tourist attractions of D'Mooat and also want to know the value of R / C ratio. The data used are primary data and secondary data. This research was conducted in November 2018 until January 2019. The research method used was a case study by taking Mooat Village, which is the only village that cultivates strawberry plants in East Bolaang Mongondow Regency. Analysis of the data used is farm analysis and R / C analysis. The results of the research showed that the receipt of strawberries in one year at the tourist site D'Mooat of 8000 polybags was Rp. 162,000,000 with an expenditure of Rp. 57,721,500 so that it gives an income of Rp 104,278,500 or Rp 8,689,875 / month with an R / C value> 2,47. Strawberry farm income is profitable because it is 2.85 times greater than the minimum monthly wage in North Sulawesi Province.*eprm*